PARASITIC INFECTION IN CAPTIVE REPTILES (SNAKES) - Satpute, Ashlesha; Jumde, Pratibha; Agrawal, A M; Singh, Uma; Bhangale, G N; Maske , D K; Deshkar, S K (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A total of 16 fecal samples of captive reptiles (snakes) of different species maintained at Rajiv Gandhi Zoological Snake Park, Katraj, Pune (M.S.), were examined. Out of 16 fecal samples examined, 8 were positive for parasitic infection. Out of total infected snakes three were found positive for Taenia sp., one Grass snake for Echinoccocus sp., one Banded racer snake was positive for Ascarid sp., one Russels viper for Trichostrongyle sp., one Common trinket snake for Strongyloide sp. and one Rat snake for Stephaneurus sp. infection.